MY GRANDCHILDREN WOULD KNOW THAT… SENIORS INTERPRETING EMOTICONS - Bielinis, Lidia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article is an attempt of presenting didactic experience related to workshops conducted with several groups of seniors in the frame of the University of Warmia and Mazury in Olsztyn (Poland) project. The main aim of the survey presented in this manuscript was to show University of Third Age students’ interpretations of emoticons and to analyse forms of communication preferred by them. The data was collected through open-ended discussions and a few tasks farmed out to seniors during the workshops. These tasks were: i) choosing the form of communication (face-to-face or mediated by a mobile device), and ii) indicating emotions, attitudes or associations related to emoticons that had been handed out to them earlier. The analysis testifies that the researched Third Age University students definitely preferred traditional, analogue forms of communication. In their opinion, face-to-face interaction surpasses daily communication processes. Surprisingly, however they were good readers of emoticons, which they owed to their grandchildren, who were perceived by them as specialists in this area.